College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.7 - Combining Functions - 2.7 Exercises: 62

Answer

$\sqrt{\frac{\sqrt[3]{x}}{\sqrt[3]{x}-1}}$

Work Step by Step

We are given: $f(x)=\sqrt{x},\ g(x)=\frac{x}{x-1},\ h(x)=\sqrt[3]{x}$ We evaluate: $(f \circ g\circ h)(x)=f(g(h(x)))= f(g(\sqrt[3]{x}))=f(\frac{\sqrt[3]{x}}{\sqrt[3]{x}-1})= \sqrt{\frac{\sqrt[3]{x}}{\sqrt[3]{x}-1}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.